Beyond Money: A Social Analysis of Happiness - HAMZAOĞLU, NAZİFE MERVE (Beykoz Üniversitesi, 2022)
As a main indicator of well-being, happiness-related studies have become an essential topic in the economics literature; the relationship between happiness and economic factors is frequently discussed. However, social well-being is not only related to economic factors such as income and employment but also social relations, status, health, and behavioral factors. In this study, I reveal social factors affecting the happiness level. Using the World Values Survey data (2017-2021), I analyzed the relationship with several social factors. The results indicate that health, security, commitment to religion, financial satisfaction, freedom of choice, having children, interests in politics, living in a secure and democratic environment, and supporting the increase of government ownership in the industry have positive and significant impacts on happiness. Moreover, the econometric model shows that young people and women tend to be happier, and marriage and income have positive and significant impacts on happiness. Also, happier people prefer TV as an information resource, but those who prefer the internet and social media to obtain information are less happy. Lastly, perceived corruption is negatively correlated with happiness.

İyi oluşun temel bir göstergesi olarak mutlulukla ilgili çalışmalar ekonomi literatüründe önemli bir konu haline gelmektedirş; mutluluk ve ekonomik faktörler arasındaki ilişki sıklıkla tartışılmaktadır. Bununla birlikte, sosyal refah sadece gelir ve istihdam gibi ekonomik faktörlerle değil, aynı zamanda sosyal ilişkiler, statü, sağlık ve davranışsal faktörlerle de ilgilidir. Bu çalışmada mutluluk düzeyini etkileyen sosyal faktörler ortaya konulmaktadır. Dünya Değerler Anketi verileri (2017-2021) kullanılarak, çeşitli sosyal faktörlerle olan ilişki çalışmada analiz edilmiştir. Sonuçlar, sağlık, güvenlik, dine bağlılık, finansal tatmin, seçim özgürlüğü, çocuk sahibi olma, siyasete ilgi duyma, güvenli ve demokratik bir ortamda yaşama ve sanayide devlet mülkiyetinin artmasını desteklemenin mutluluk seviyesi üzerinde olumlu ve önemli etkileri olduğunu göstermektedir. Ayrıca, gençlerin ve kadınların daha mutlu olma eğiliminde olduğu; evlilik ve gelirin mutluluk üzerinde olumlu ve önemli etkileri olduğu görülmektedir. Çalışmaya göre daha mutlu insanlar bilgi kaynağı olarak televizyonu tercih ederken, bilgi edinmek için internet ve sosyal medyayı tercih edenler daha az mutludur. Son olarak, algılanan yolsuzluk mutlulukla negatif ilişkilidir.
Paranın Ötesinde: Mutluluğun Sosyal Bir Analizi
▪ JEL Codes: D91, D12, D63.
Keywords: Happiness Economics; Social Well-being; Behavioral Economics; Welfare